2015
DOI: 10.1097/dcc.0000000000000118
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Practices and Lead Selection in Monitoring for Myocardial Ischemia

Abstract: Continuous, 5-lead ECG monitoring is an active process that requires clinical decision making by the nurse and is not a passive activity. Registered nurses in this sample demonstrated a lack of knowledge regarding ECG monitoring for ischemia that was improved with an online educational intervention and reported intentional daily practice pattern changes postintervention testing. A unit-level intervention driven by nurses may be successful at improving fellow RNs' knowledge and evidence-based practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 2 publications
0
17
0
3
Order By: Relevance
“…In this study, nurses interviewed mentioned that having additional training every two years was insufficient to maintain their sense of proficiency in ECG interpretation due to lack of exposure, with one participant saying, ‘once I left the classroom, I never saw it again’ (Nickasch, 2016, p. 421). Seven quantitative studies identified improvement in nurses’ confidence, comfort or perception in ECG interpretation (Blakeman et al, 2015; Brooks et al, 2016; Sangkachand et al, 2011; Spiva et al, 2012; Tai et al, 2012; Throndson & Davis, 2015; Wilson et al, 2012), along with an increase in mean ECG knowledge scores after educational interventions. Only one study demonstrated no correlation between previous ECG education and ambulance nurses’ ECG interpretation skills (Werner et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, nurses interviewed mentioned that having additional training every two years was insufficient to maintain their sense of proficiency in ECG interpretation due to lack of exposure, with one participant saying, ‘once I left the classroom, I never saw it again’ (Nickasch, 2016, p. 421). Seven quantitative studies identified improvement in nurses’ confidence, comfort or perception in ECG interpretation (Blakeman et al, 2015; Brooks et al, 2016; Sangkachand et al, 2011; Spiva et al, 2012; Tai et al, 2012; Throndson & Davis, 2015; Wilson et al, 2012), along with an increase in mean ECG knowledge scores after educational interventions. Only one study demonstrated no correlation between previous ECG education and ambulance nurses’ ECG interpretation skills (Werner et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Five assessment tools focused on knowledge and perceptions of or confidence in ECG interpretation (Fålun et al, 2020; Koning et al, 2019; Spiva et al, 2012; Throndson & Davis, 2015; Wilson et al, 2012). Three tools explored ECG knowledge and practice patterns (Blakeman et al, 2015; Thomason et al, 1995; Zhou et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the PULSE trial, accuracy of documented arrhythmia interpretation by nurses improved from 82% correct to 97% after an interactive online electrocardiographic monitoring education program in the experimental group. 6 Both nurses 465,466 and physicians 467,468 report a significant increase in knowledge with an educational intervention for electrocardiographic monitoring.…”
Section: Education Of Staffmentioning
confidence: 99%
“…A good understanding of how to review alarm data and trends can also help RNs realize which alarms require immediate attention [31]. Suggestions to improve RNs' knowledge include online education [32]. This is similar to the suggestion by the American Association of Critical Care Nurses that retraining RNs on individualizing alarm parameters may help reduce inactionable alarms [8].…”
Section: Nurse and Patient Educationmentioning
confidence: 99%